Growth, Physiological, and Photosynthetic Responses of Xanthoceras sorbifolium Bunge Seedlings Under Various Degrees of Salinity - Zong, Jian-Wei; Zhang, Zhi-Long; Huang, Pei-Lu; Chen, Nai-Yu; Xue, Ke-Xin; Tian, Zhi-Yong; Yang, Yu-Hua (Frontiers in Plant Science, 2021)
Xanthoceras sorbifolium Bunge is priced for its medical and energetic values. The species also plays a key role in stabilizing ecologically fragile areas exposed to excess soil salinity. In this study, effects of salinity on the growth, physiological and photosynthetic parameters of Xanthoceras sorbifolium Bunge were investigated. The Xanthoceras sorbifolium seedlings were subjected to four salt treatments: 0 (CK), 70, 140, 210 and 280mM of sodium chloride (NaCl) solutions. NaCl caused a decrease in plant height, specific leaf area, biomass and root parameters. Leaf wilting and shedding, and changes in root morphology, such as root length, root surface area and root tips were observed. Our study found that Xanthoceras sorbifolium is tolerant to high salinity. Compared to the control (CK) group, even if the concentration of NaCl was higher than 210mM, the increase of the relative conductivity was also slow, while intercellular CO2 concentration had a similar trend. Moreover, NaCl stress caused an increase in the malondialdehyde (MDA), soluble proteins and the proline. Among the enzymes in the plant, the catalase (CAT) activity increases first and decreased with the increase in the intensity of NaCl stress, but salt treatment had no significant effect on superoxide dismutase (SOD) activity. The peroxidase (POD) showed increasing trend under salt stress. It was found that the photosynthesis of Xanthoceras sorbifolia was notably impacted by saline stress. NaCl toxicity induced a noticeable influence on leaf net photosynthetic rate (Pn), stomatal conductance(Gs), intercellular CO2 concentration(Ci), transpiration rate(E), and water use efficiency(Wue). As salt concentration increased, the content of chlorophyll decreased. It can be found that a low concentration of NaCl induced the increase of photosynthetic capacity but a high intensity exposure to stress resulted in the reduction of photosynthetic efficiency and SOD activity, which had a positive correlation. To sum up, salt-induced ionic stress primarily controlled root morphology, osmotic adjustment, and enzyme activities of salt-treated Xanthoceras sorbifolium leaves, whereas the low salt load could in fact promote the growth of roots.